Quantitative measures of lambs fed hydrolyzed sugarcane under aerobic and anaerobic conditions - Endo, Viviane [UNESP]; Silva Sobrinho, Americo Garcia da [UNESP]; Lins Lima, Natalia Ludmila [UNESP]; Almeida, Fabiana Alves de [UNESP]; Brancacci Lopes Zeola, Nivea Maria [UNESP] (Univ Estadual Londrina, 2015)
This study aimed to evaluate the influence of aerobic and anaerobic conditions on hydrolyzed sugarcane, over the in vivo morphological measurements, quantitative traits of carcass and non-carcass components of lambs. Twenty four Ile de France lambs, from 15 to 32 kg of body weight (BW) were used. Treatments were: in natura sugarcane (IN), sugarcane hydrolyzed using 0.6% calcium oxide (CaO) under aerobic condition (AER), and sugarcane hydrolyzed using 0.6% CaO under anaerobic condition (ANA). Treatments were supplied to animals along with concentrate. Before slaughtering, the lambs were weighed and morphological measurements were taken. After slaughtering, carcasses were evaluated for weight, dressing, non-carcass components, as well as their morphological measurements and weight loss by cooling. A completely randomized design with three treatments and eight replicates was used and the means were compared by Tukey test at 5% of significance. Lambs fed hydrolyzed sugarcane in aerobic condition had higher leg length (32.21 cm) and lower rump height (55.23 cm) in vivo, whereas empty body weight (24.84 kg) was lower for lambs fed in natura sugarcane. No difference for the other variables was observed. Sugarcane hydrolyzed under aerobic and anaerobic conditions is not an important factor affecting the in vivo, neither the carcass measurements of the animals. The choice between supplying in natura or hydrolyzed sugarcane will depend on an economic analysis.

Este estudo teve como objetivo avaliar a influência das condições aeróbicas e anaeróbicas da cana-deaçúcar hidrolisada sobre as medidas morfológicas in vivo, características quantitativas da carcaça, e os não-componentes da carcaça de cordeiros. Foram utilizados 24 cordeiros Ile de France dos 15 aos 32 kg de peso corporal (PC). Os tratamentos foram: cana-de-açúcar in natura (IN), cana-de-açúcar hidrolisada com 0,6% de óxido de cálcio (CaO) em condição aeróbica (AER), e cana-de-açúcar hidrolisada com 0,6% de CaO em condição anaeróbica (ANA). Os tratamentos foram suplementados com concentrado. Antes do abate, os cordeiros foram pesados e foram obtidas as medidas morfológicas. Após o abate, as carcaças foram pesadas e avaliadas para rendimento, não-componentes, assim como suas medidas morfológicas e perda de peso por resfriamento. Foi utilizado o delineamento inteiramente casualizado com três tratamentos e oito repetições. As médias foram comparadas pelo teste de Tukey a 5% de significância. Cordeiros alimentados com cana-de-açúcar hidrolisada em condição aeróbica, que tiveram maior comprimento de perna (32.21 cm) e menor altura de garupa (55.23 cm) in vivo, Enquanto que o peso corporal vazio (24.84 kg) foi inferior para cordeiros alimentados com cana-deaçúcar in natura. Não foi observada diferença para as demais variáveis. A cana-de-açúcar hidrolisada em condições aeróbica e anaeróbica não é um fator importante em afetar as características in vivo, nem as medidas da carcaça de cordeiros. A escolha entre o fornecimento da cana-de-açúcar in natura ou hidrolisada dependerá de uma análise econômica.
Características quantitativas de cordeiros alimentados com cana-deaçúcar hidrolisada em condições aeróbica e anaeróbica
Keywords: Hydrolysis; Morphology; Dressing; Saccharum officinarum; Hidrólise; Morfologia; Rendimento; Saccharum officinarum